The Economic Effects of Adopting a Right-to-Work Law: Implications for Illinois. (December 2015) - Bruno, Robert; Zullo, Roland; Manzo, Frank; Dickson, Alison
While considerable efforts have been made by legislators, business associations, and political organizations to pass right-to-work (RTW) laws in states across the country, the empirical evidence on the effect of adopting an RTW law on labor market outcomes and state budgets is both varied and mixed. This article provides a forecast on the effect of RTW laws on important labor market outcomes—including earnings, employment, unionization, and inequality. It also investigates RTW's impacts on two particularly affected industries (manufacturing and construction) and three demographic groups (African-American, Latino/a, and female workers). The findings are subsequently applied to the state of Illinois to project the potential law's impact on Illinois workers and on the state's tax revenues. By and large, as a policy prescription, RTW would generate harmful effects to Illinois' economy, lower its capacity to provide essential public services and degrade the quality and condition of the state's labor force.